LGBTQ+ Persons' Experiences of Parenthood in the Context of Maternal and Child Health Care: A Meta-ethnography - Charlotte Haugland; Bente Kristin Høgmo; Terese Elisabet Bondas (SAGE Publishing, 2023)
This study aims to integrate and synthesize knowledge of lesbian, gay, bisexual, transgender and queer (LGBTQ+) persons' experiences of parenthood in the context of maternal and child health care. For nurses to provide optimal care for LGBTQ+ parents, we need to derive knowledge from their perspectives. An interpretive meta-synthesis approach, meta-ethnography, was chosen for this study. A lines-of-argument synthesis based on four themes was developed: (1) Entering the world of LGBTQ+ parenthood; (2) The emotional journey in LGBTQ+ parenthood; (3) Struggling with the system as a LGBTQ+ parent and (4) A need to expand the knowledge horizon of LGBTQ+ parenthood. The overarching metaphor, "To be recognised as parents, unique and good enough, like everybody else," reflects how recognition and inclusion may support LGBTQ+ persons in their parenthood and broaden the understanding of parenthood. Knowledge of the LGBTQ+ family needs to be given greater attention in maternity and child health care settings, and in education and health policies.